Constitutional law implications of the implementation of attorney general regulation number 15 of 2020 for crime victims - Farida Tuharea; Wahyudi BR; Andi Annisa Nurlia Mamonto; Liani Sari (Institute Of computer Science (IOCS), 2024)
This research aims to examine the effects of Attorney General’s Regulation (PERJA) Number 15 of 2020 on Indonesian Constitutional Law, specifically examining victim rights and responsibilities and elements of legal certainty in relation to the Termination of Prosecution Based on Restorative Justice. Human rights, victim protection, and procedural justice are some of the Constitutional Law elements that are examined in this study. This study combines philosophical and analytical approaches to normative law with a critical and logical examination of applicable legal theory and police tactics. The relevant rules and statutes are described using analytical descriptive methodologies. Despite presenting obstacles to legal certainty owing to its flexible approach, the study findings demonstrate that the adoption of restorative justice via the Attorney General's Regulation has significantly increased victims' rights in the recovery and reconciliation process. To promote a shift in Indonesia's criminal justice system towards a greater emphasis on justice, victim healing, and societal interests, the Attorney General's Regulation seeks to strike a balance by outlining a clear framework.